Effects of monochromatic lights on the growth and antioxidant enzyme activity of Sanghuangporus sanghuang - WANG Yuzhen; MA Yao; CHEN Qi; MA Hongyan; YANG Jing; LIU Chen; LI Junzhi; MA Xiaokui (浙江大学学报. 农业与生命科学版)
This study aimed to explore the influence of different monochromatic lights on the growth and antioxidant enzyme activity of the mycelia of fungus Sanghuangporus sanghuang. We used a light emitting diode (LED) -based light source as a monochromatic light source, including the blue light (455-490 nm), green light (515-540 nm), yellow light (580-600 nm) and red light (610-710 nm), and taking the white light (390-710 nm) as a control. The growth status, morphological characteristics, malondialdehyde (MDA) content and the activities of superoxide dismutase (SOD) and catalase (CAT) of this strain were studied under the irradiation of different monochromatic lights. The results indicated that, compared with those under the white light, the colony diameter of S. sanghuang increased significantly and the mycelia were denser under the red light, and the fungal growth was inhibited under the blue light and green light, but there was a minimal impact on the fungal growth under the yellow light. The SOD activity of mycelium increased significantly after 9 d of irradiation under the blue light, green light and yellow light, respectively (P<0.05), while it decreased significantly after 3 d of irradiation under the red light. The CAT activity of mycelium increased under the four monochromatic lights. On the 11th day, the CAT activity increased significantly (P<0.05), reaching to (31.82±1.60) U/(g•min) under the yellow light. The highest MDA content was observed under the blue light on the 9th day, reaching to (1.07±0.03) mmol/g, which was around 1.16 times under the white light; however, no significant change in the MDA content was observed under the other monochromatic lights. In summary, different monochromatic lights impose different influences on the growth and antioxidant enzyme activity of S. sanghuang, and the red light is more favorable for the growth than the other tested lights.